2010
DOI: 10.1016/j.neulet.2009.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Theta and alpha oscillations during working-memory maintenance predict successful long-term memory encoding

Abstract: To date, much is known about the neural mechanisms underlying working-memory (WM) maintenance and long-term-memory (LTM) encoding. However, these topics have typically been examined in isolation, and little is known about how these processes might interact. Here, we investigated whether EEG oscillations arising specifically during the delay of a delayed matching-to-sample task reflect successful LTM encoding. Given previous findings of increased alpha and theta power with increasing WM load, together with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
126
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 39 publications
23
126
1
Order By: Relevance
“…Related results have been found in an EEG study using letter strings and line drawings as memory items [Khader et al, 2010]. Other studies found a decrease in alpha activity during presentation of the stimuli to correlate with successful encoding in LTM [Hanslmayr et al, 2009;Klimesch et al, 1996b;Sederberg et al, 2007;Weiss and Rappelsberger, 2000].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Related results have been found in an EEG study using letter strings and line drawings as memory items [Khader et al, 2010]. Other studies found a decrease in alpha activity during presentation of the stimuli to correlate with successful encoding in LTM [Hanslmayr et al, 2009;Klimesch et al, 1996b;Sederberg et al, 2007;Weiss and Rappelsberger, 2000].…”
Section: Discussionsupporting
confidence: 69%
“…In particular, increased alpha activity in task-irrelevant regions was related to optimal performance in a somatosensory working memory task [Haegens et al, 2009]. A recent EEG study reported stronger alpha activity associated with LTM encoding of objects and letter strings [Khader et al, 2010].…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, as Takashima et al (2006) concluded from an MEG study of the encoding of complex scenes, working memory processes associated with deep perceptual and semantic processing appear to act in tandem with top-down modulation of contextually constrained visual perception to promote successful declarative memory formation. This notion of continuously interacting memory systems is also consistent with the role of oscillatory phase synchronization between different brain regions in supporting interactions between working memory and long-term memory storage (Fell and Axmacher, 2011; see also Khader et al, 2010). We propose that these emerging ideas suggest that 'tuning up' perceptual and semantic processing and working memory capacity through implicit learning and/or repetitive practice may be the optimal approach to fixing broken explicit learning and memory systems in neuropsychiatrically impaired brains.…”
Section: Cognitive Training Must Focus On Implicit Learning Mechanismssupporting
confidence: 72%
“…The study found statistically significant higher brainwave activity in the beta, delta, and gamma bands for 2D images and in the alpha and theta bands during 3D projection. It has previously been reported that activity in the theta and alpha bands is indicative of global information transfer and relates to memory function, attention, and decisionmaking 15,16 . It may be that the human brain interprets 2D and perspective 3D images similarly, but differently to projected 3D, as they are dependent on stereopsis.…”
Section: Discussionmentioning
confidence: 99%